2019
DOI: 10.1038/s41467-019-12123-7
|View full text |Cite
|
Sign up to set email alerts
|

UPF1/SMG7-dependent microRNA-mediated gene regulation

Abstract: The stability and quality of metazoan mRNAs are under microRNA (miRNA)-mediated and nonsense-mediated control. Although UPF1, a core mediator of nonsense-mediated mRNA decay (NMD), mediates the decay of target mRNA in a 3′UTR-length-dependent manner, the detailed mechanism remains unclear. Here, we suggest that 3′UTR-length-dependent mRNA decay is not mediated by nonsense mRNAs but rather by miRNAs that downregulate target mRNAs via Ago-associated UPF1/SMG7. Global analyses of mRNAs in response to UPF1 RNA int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 64 publications
0
21
0
Order By: Relevance
“…Whether SMG7 targets these transcripts on its own or in concert with other NMD proteins remains to be determined. SMG7 alone may contain the capacity to degrade RNA transcripts via interaction with CNOT8 [11] and can also degrade 3′ UTR length‐dependent mRNA via UPF1/SMG7‐dependent miRNA‐mediated mRNA decay pathway [48]. Screening results of other NMD factors, in contrast to Smg7 , did not reveal protection against TNFα (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Whether SMG7 targets these transcripts on its own or in concert with other NMD proteins remains to be determined. SMG7 alone may contain the capacity to degrade RNA transcripts via interaction with CNOT8 [11] and can also degrade 3′ UTR length‐dependent mRNA via UPF1/SMG7‐dependent miRNA‐mediated mRNA decay pathway [48]. Screening results of other NMD factors, in contrast to Smg7 , did not reveal protection against TNFα (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…A considerable proportion of CUG motifs were embedded in miRNA 7mer sites of abundant miRNA families and such miRNA target mRNAs were significantly upregulated in UPF1-depleted cells. This effect disappeared when the CUG motif was mutated and upon depletion or deletion of Dicer, suggesting a correlation between miRNA- and UPF1-mediated decay [ 200 ]. UPF1 and AGO binding sites have previously been shown to overlap [ 124 ].…”
Section: Upf1/smg7/mirna-mediated Mrna Decay (Upf1/smg7/mirna-md)mentioning
confidence: 99%
“…SMG7 is recruited by UPF1 to a complex that also contains AGO and interacts with deadenylase complex components NOT1 and NOT3 in a SMG7 dependent manner. However, other than in the canonical miRNA pathway, GW182 (also known as TNRC6A/C) is not required for the interaction with the CCR4/NOT complex, indicating that UPF1/SMG7-dependent miRNA-mediated gene regulation may constitute an alternative miRNA targeting pathway [ 200 ]. UPF1/SMG7/miRNA-mediated mRNA decay has been dubbed UPF1-mediated decay (UMD) by its discoverers who posit that this decay pathway, rather than NMD, is the norm for EJC-independent degradation of mRNAs with long 3′UTRs and degrades between 40% and 50% of all error-free NMD substrates [ 200 ].…”
Section: Upf1/smg7/mirna-mediated Mrna Decay (Upf1/smg7/mirna-md)mentioning
confidence: 99%
See 1 more Smart Citation
“…miRNA is a type of noncoding RNA with regulatory functions in eukaryotes. It is ~20–25 nt in length and can specifically bind to the 3′ untranslated region (3′UTR) of the target genes in order to regulate their expressions 18 . Studies have shown that miR-651-3p negatively regulates TIAM1, which is highly expressed in gastric cancer cells 19 .…”
Section: Introductionmentioning
confidence: 99%